2021
DOI: 10.1093/tas/txab004
|View full text |Cite
|
Sign up to set email alerts
|

Peroral iron supplementation can be provided to piglets through a milk cup system with results comparable to parenteral iron administration

Abstract: The objective of this study was to investigate if iron can be allocated to piglets through sow milk replacer fed in a milk cup system with efficacies comparable to intramuscular (IM) administration of 200 mg gleptoferron. Two hundred and ninety-four piglets from 21 litters were allocated to three different iron treatments (n = 98). The treatments were 1) Control (CON) provided no supplemental iron, 2) Injected iron (II) provided 200 mg gleptoferron IM on day 3 postpartum, and 3) Milk iron (MI) provided sow mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Hemoglobin and MCHC concentrations are used as indicators of anemia, which, in piglets, is often regarded as a result of iron deficiency. Neither the MILK nor the SOW group were given iron injections, and their hemoglobin levels were just as low as observed in other studies where iron injections were also not provided [ 26 ] and where both groups would classify as anemic [ 26 , 27 ]. The neutrophil levels in the MILK compared with the SOW group are low, suggesting that they have transferred to the tissue, and when carefully interpreted, the respective relationships between lymphocytes and neutrophils could indicate different stages of maturation of the innate and adaptive immune system between SOW and MILK piglets.…”
Section: Discussionmentioning
confidence: 79%
“…Hemoglobin and MCHC concentrations are used as indicators of anemia, which, in piglets, is often regarded as a result of iron deficiency. Neither the MILK nor the SOW group were given iron injections, and their hemoglobin levels were just as low as observed in other studies where iron injections were also not provided [ 26 ] and where both groups would classify as anemic [ 26 , 27 ]. The neutrophil levels in the MILK compared with the SOW group are low, suggesting that they have transferred to the tissue, and when carefully interpreted, the respective relationships between lymphocytes and neutrophils could indicate different stages of maturation of the innate and adaptive immune system between SOW and MILK piglets.…”
Section: Discussionmentioning
confidence: 79%
“…These feed intakes are much greater than what was found in the present study, which might be explained by the fact that in Bruininx et al [ 19 , 22 ] the pigs had four days more to consume the feed due to longer pre-weaning period, whereas 60–65% of the feed was consumed from day 22–28 in these studies. Furthermore, in the previous studies the pigs had access to feed 24 h a day, whereas in the present study pigs had access to creep feed from 0800 to 1700 h. As it was not possible to provide fresh liquid creep feed for 24 h due to on-farm limitations, the daily period of feed provision was based on the study by Jakobsen et al [ 18 ] reporting that pigs visit the feeder more frequently during this interval, and thus increasing the chance of greater feed consumption. Toplis et al [ 17 ] reported a DM intake in the pre-weaning period from day 14–24 to be a total of 91 g DM per pig when fed a dry pelleted diet, and 374 g DM per pig when fed a liquid diet (1:2 feed-to-water ratio) where the feed was available 24 h a day.…”
Section: Discussionmentioning
confidence: 98%
“…The feed was provided in a plastic creep feeder (Hatting, Denmark) that was fixed to the slats in the floor next to the nipple drinker within each pen. Creep feed was offered 9 times a day in one-hour intervals from 0800 to 1600 h, thus the pigs had access to feed from 0800 to 1700 h. This time frame was decided upon due to previous observations on piglet feeding behavior [ 18 ] and in order to keep the liquid feed fresh. The creep feeders were manually cleaned every hour and new feed was provided.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Yu et al [ 9 ] suggested that creep feeding with 175 mg Fe/kg diet from d 7 of age might contribute the certain amount of iron to the piglets for sufficient overall growth while there was a numerically lower growth rate, significantly lower serum iron and hemoglobin levels in no additional iron injection treatment compared with the additional iron injection treatments. Due to low absorption rate and less tissue retention of iron administered orally [ 10 , 11 ], an additional iron injection before weaning might be needed to improve hematological status and potentially growth of piglets [ 12 , 13 , 14 ] when the pigs are weaned at over 26–28 d of age although an additional iron injection could be laborious in the pig production [ 15 ]. Furthermore, it has not been demonstrated yet whether the effectiveness of additional iron injection depends on the hematological status of piglets at the administration that are dependent on the level of the first iron injection at birth [ 14 ] and the amount of iron additionally administered to piglets prior to weaning [ 6 ].…”
Section: Introductionmentioning
confidence: 99%